A new species of Formosiepyris Terayama, 2004 (Hymenoptera: Bethylidae) from China - Xu, Zaifu; He, Junhua (Zootaxa, 2005)
A new species of the genus Formosiepyris Terayama, 2004 is described from Fujian Province, China. A key to the species of Formosiepyris is given.